Effect of magnesium sulphate on the first stage of development of Lucerne - Abid M.; Haddad M.; Ferchichi A. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
In the south of Tunisia, the water used in irrigation, especially geothermic water, is rich in sulphates. The objective of this study was to evaluate the effect of increasing concentrations of magnesium sulphate (MgSO4) from 0 to 5 g/l on the development of alfalfa (Medicago sativa L.) during its first stages of growth. Results showed that: (i) a high level of germination (>90%) was detected even at high concentrations, however, a concentration of 5 g/l of MgSO4 produced a delay in the germination stage of 36 hours; and (ii) high concentrations resulted in decreased production (88% for a concentration of 5 g/l).
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)